Konsep Implementasi Bisnis Multi Level Marketing (Mlm) Berdasarkan Tinjauan Fiqih Muamalah dengan Penerapan Nilai-Nilai Islam Berlandaskan Alqur'an dan Hadist - lutfiah fajrianti (Program Pascasarjana IAIN Langsa, 2022)
In the business world, it is often found in businesses that contain elements of usury in them which makes many people tempted to take part in accepting it because the income obtained exceeds the specified principal limit. However, there are still many people who do not understand the dangers of a business that contains elements of usury. This business practice is not only common among large companies, but also among small people who really want more income than usual. One of these businesses is Multi Level Marketing or abbreviated as MLM which is still being discussed by business people in Indonesia. This system is really lucrative because it can guarantee success and offer riches in a relatively short time. However, the small community certainly needs to know or understand what provisions need to be applied based on a review of muamalah fiqh. Implementation of any business that is permitted and forbidden. Especially as a Muslim who wants to do business and run a business, these business people need to have understood and also implemented Islamic values ​​based on the Qur'an and Hadith.